Retrospective analyses of other iatrogenic immunodeficiency‐associated lymphoproliferative disorders in patients with rheumatic diseases. (23rd September 2021) - Kaji, Daisuke; Kusakabe, Manabu; Sakata‐Yanagimoto, Mamiko; Makishima, Kenichi; Suehara, Yasuhito; Hattori, Keiichiro; Ota, Yasunori; Mitsuki, Takashi; Yuasa, Mitsuhiro; Kageyama, Kosei; Taya, Yuki; Nishida, Aya; et al.
Summary: Other iatrogenic immunodeficiency‐associated lymphoproliferative disorders (OIIA‐LPDs) occur in patients receiving immunosuppressive drugs for autoimmune diseases; however, their clinicopathological and genetic features remain unknown. In the present study, we analysed 67 patients with OIIA‐LPDs, including 36 with diffuse large B‐cell lymphoma (DLBCL)‐type and 19 with Hodgkin lymphoma (HL)‐type. After discontinuation of immunosuppressive drugs, regression without relapse was achieved in 22 of 58 patients. Spontaneous regression was associated with Epstein–Barr virus positivity in DLBCL‐type ( P = 0·013). The 2‐year overall survival and progression‐free survival (PFS) at a median follow‐up of 32·4 months were 92·7% and 72·1% respectively. Furthermore, a significant difference in the 2‐year PFS was seen between patients with DLBCL‐type and HL‐type OIIA‐LPDs (81·0% vs. 40·9% respectively, P = 0·021). In targeted sequencing of 47 genes in tumour‐derived DNA from 20 DLBCL‐type OIIA‐LPD samples, histone‐lysine N ‐methyltransferase 2D ( KMT2D ; eight, 40%) and tumour necrosis factor receptor superfamily member 14 ( TNFRSF14 ; six, 30%) were the most frequently mutated genes. TNF alpha‐induced protein 3 ( TNFAIP3 ) mutations were present in four patients (20%) with DLBCL‐type OIIA‐LPD. Cases with DLBCL‐type OIIA‐LPD harbouring TNFAIP3 mutations had shorter PFS and required early initiation of first chemotherapy. There were no significant factors for spontaneous regression or response rates according to the presence of mutations. Overall, OIIA‐LPDs, especially DLBCL‐types, showed favourable prognoses.